Penilaian Kinerja Keuangan PT. HM. Sampoerna Sebelum dan Sesudah di Akuisisi oleh PT. Philip Moris International dengan Menggunakan Metode Economic Value Added (EVA) - Linda, Muthia Roza; Megawati, Megawati (Jurnal Kajian Manajemen Bisnis, 2012)
This research aimed to determine whether the acquisitions made by PT. Phillip Moris Internationan for PT. HM Sampoerna gives value added to the financial performance of PT. HM Sampoerna. This research uses secondary data from PT. HM Sampoerna financial statement for 5 years prior to acquisition (2000 – 2004) and 5 years after acquisition (2006 – 2010). Financial statement in 2005 was not used because of the acquisition process conducted during the period. An analytical model used in this research is called the Economic Value Added (EVA). EVA is the value created by company activities during a specific period. There is a major drawback if we use financial ratio analysis as a measure of financial performance, namely ignoring the cost of capital, making it difficult to know whether the company has managed to create value added or not. The result also indicate that the acquisition by PT. Phillip Moris International for PT. HM Sampoerna providing value added to corporate value which is described by the increasing trend of EVA every years.